A retrospective study of neonatal case management and outcomes in rural Rwanda post implementation of a national neonatal care package for sick and small infants - Nyishime, Merab (BMC Pediatr, 2018)
BACKGROUND: Despite worldwide efforts to reduce neonatal mortality, 44% of under-five deaths occur in the first 28 days of life. The primary causes of neonatal death are preventable or treatable. This study describes the presentation, management and outcomes of hospitalized newborns admitted to the neonatal units of two rural district hospitals in Rwanda after the 2012 launch of a national neonatal protocol and standards. METHODS: We retrospectively reviewed routinely collected data for all neonates (0 to 28 days) admitted to the neonatal units at Rwinkwavu and Kirehe District Hospitals from January 1, 2013 to December 31, 2014. Data on demographic and clinical characteristics, clinical management, and outcomes were analyzed using median and interquartile ranges for continuous data and frequencies and proportions for categorical data. Clinical management and outcome variables were stratified by birth weight and differences between low birth weight (LBW) and normal birth weight (NBW) neonates were assessed using Fisher’s exact or Wilcoxon rank-sum tests at the α = 0.05 significance level. RESULTS: A total of 1723 neonates were hospitalized over the two-year study period; 88.7% were admitted within the first 48 h of life, 58.4% were male, 53.8% had normal birth weight and 36.4% were born premature. Prematurity (27.8%), neonatal infection (23.6%) and asphyxia (20.2%) were the top three primary diagnoses. Per national protocol, vital signs were assessed every 3 h within the first 48 h for 82.6% of neonates (n = 965/1168) and 93.4% (n = 312/334) of neonates with infection received antibiotics. The overall mortality rate was 13.3% (n = 185/1386) and preterm/LBW infants had similar mortality rate to NBW infants (14.7 and 12.2% respectively, p = 0.131). The average length of stay in the neonatal unit was 5 days. CONCLUSIONS: Our results suggest that it is possible to provide specialized neonatal care for both LBW and NBW high-risk neonates in resource-limited settings. Despite implementation challenges, with the introduction of the neonatal care package and defined clinical standards these most vulnerable patients showed survival rates comparable to or higher than neighboring countries.